The Impact of Credit Risk Management Indicators on Profitability Attributes: Evidence from the State-Owned Commercial Banks in Bangladesh - Banu, Mst. Hasna; Sayaduzzaman, Md.; Sil, Subhash Chandra (American Journal of Trade and Policy, 2021)
The focal attempt of this research is to identify the consequence of credit risk management indicators on profitableness attributes of state-owned commercial banks functioning in Bangladesh. To attain the objectives of this research study researcher has analyzed four sample banks’ audited annual reports covering the period 2012 to 2016. The study has employed the ANOVA technique, multiple regression model, and correlation matrix to reach the concluding remark as per study objectives. The findings revealed that there is significant and insignificant variation as well as relationship in the different indicators of credit risk management but there is insignificant variation in the different attributes of profitability in the midst of the sample banks within the study period. Furthermore, there is the insignificant impact of the different indicators of credit risk management namely loan and advance, classified loan, unclassified loan, leverage ratio, bad debt, default ratio, cost per loan asset, and cost to income ratio on profitability attributes such as return on assets, return on equity along with net profit percentage of the sample banks over the study period. Hence, the study has recommended that the management of the banking sector should emphasize creating a smart credit management policy as well as lending guidelines to formulate the suitable credit risk management practice to meet the demand of loans applicants properly.